Sexual Dimorphism in Red-Eared Sliders (Trachemys scripta elegans) from the Wild Animal Triage Center of the Tiete Ecological Park, São Paulo, Brazil - Gradela, Adriana; Santiago, Thamyris Oliveira Carneiro; Pires, Isabelle Caroline; Silva, Alequisandra de Castro Souza; Souza, Leniker Cordeiro de; Faria, Marcelo Domingues de; Neto, Joaquim Pereira; Milanelo, Liliane (Acta Scientiae Veterinariae, 2017)
Background: Trachemys scripta elegans is an aquatic turtle native to North America and distributed geographically from the eastern United States to northeastern Mexico. In Brazil, it is an exotic and invasive species and the most illegally traded pet animal. When these turtles grow and they cease to be attractive as pets, they are released clandestinely in lakes, ponds, rivers, and other bodies of water, where they threaten biodiversity and native populations. The present study aimed to characterize specimens of T. s. elegans from the Centro de Triagem de Animais Silvestres do Parque Ecológico do Tiete by analyzing body biometrics, sexual dimorphism, and structure of specimens for sex ratio and size classes. Materials, Methods & Results: Trachemys scripta elegans turtles (39 females and 30 males) were anesthetized, euthanized and frozen. After being thawed, the turtles were sexed according to measurements on secondary sex characters such as claw length (CWL) of the third finger of the right forearm and length of the tail from the tip to the beginning of the cloacal opening (postcloacal tail length, PTL); subsequently, sex was confirmed through dissection. Subsequently, body mass (BM, g) and maximum carapace length (MCL, cm), maximum carapace width (MCW, cm), maximum plastron length (MPL, cm), maximum plastron width (MPW) and shell height (HGT, cm, measured laterally until obtaining the greatest value) were evaluated and the sexual dimorphism index (SDI) was also calculated. All analyses were performed using SAS v. 9.4 software. The results indicate a sex ratio of 1.3 females per male. The identification of males by secondary sex characteristics was performed using only claw length (CWL), which was related to sex and not to maximum carapace length (MCL). The most discriminatory variables were CWL in males and body mass (BM) in females. With the exception of CWL, the sexual dimorphism index (SDI) values all favored females and varied from 1.21 to 2.49, with the greatest value for BM and the lowest value for postcloacal tail length (PTL). Males exhibited a unimodal tendency at a classification interval of 15.0 cm MCL, and females exhibited a bimodal tendency at 21.0- and 22.0 cm MCL. Sexual maturity was identified at 12.0 cm MCL in males and at 12.5 cm MCL in females. The rate of CWL growth in males was higher at the beginning of sexual maturity and subsequently decreased, whereas in females, the rate of CWL escalated after 19.0 cm MCL. In both sexes, principal component 1 (PC1) was composed of the variables related to size and BM, and principal component 2 (PC2) and principal component 3 (PC3) were composed of variables related to secondary sex characteristics (CWL and PTL). Discussion: In members of the genus Trachemys, several secondary sex characteristics can be used to differentiate between the sexes, however, in the present study, recognition of males was performed only by claw length, as it was confirmed by the discriminate analysis and the principal components analysis (PCA) which showed that CWL was the variable that was most discriminatory in males (approximately 76.0%), followed by BM (approximately 50%) in females. The results reinforcing the claim that the degree of development of secondary sex characteristics varies between species as well as between distinct populations of the same species and establish that even under unnatural habitat, sexual dimorphism of size in favor of females is maintained for variables related to mass and size.